Globalization and Female Labor Force Participation in Developing Countries: An Empirical (Re-)Assessment - Arusha Cooray; Isis Gaddis; Konstantin M. Wacker (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2012)
We investigate the impact of foreign direct investment (FDI) and trade, as two measures of globalization, on female labor force participation in a sample of 80 developing countries over the last decades. Contrary to the mainstream view in the literature, which is mainly based on country-case studies or simple cross-country variation, we find that both, FDI and trade have a generally negative impact on female labor force participation. While the impact is of negligible economic size, it is stronger for younger cohorts, potentially reflecting a higher incentive to stay out of the labor force and invest in education in view of an increased skill premium due to globalization. We also find that the direction of the effect depends on the industrial structure of the economy. This suggests that there is no evidence of a (conditional) anti-female bias in multinational corporations' factor demand once one controls for the interaction of FDI with the size of the agricultural sector. We can thereby explain why country studies find other effects and question the generalization of their results into an overarching globalization tale concerning female labor force participation.
Keywords: F0; J22; O1; 330; Globalization; Labor Force Participation; FDI; Trade; Development; Hierarchical Panel Data Models